Antioxidant activity of the new black vinegar “IZUMI” - Nagashima, M.; Saito, K. (The Journal of nutrition, health & aging, 2010)
“IZUMI” is a new kind of vinegar resulting from an improvement in the manufacturing method of Kurosu, a traditional vinegar product made from unpolished rice. We evaluated the antioxidant activity of this new Kurosu by means of measuring the level of diacron-reactive oxygen metabolites (d-ROM), the biological antioxidant potential (BAP), as well as RBC deformability using the microchannel array flow method. Ten healthy, untrained female volunteers participated in this study. Measurements: All subjects drank 50 ml of “IZUMI” on a daily basis, and blood samples were collected pre-“IZUMI” (I), after one month “IZUMI” consumption (II), and after two months “IZUMI” consumption (III). The subjects continuously wore a lifecorder during a 7-day period and the nutritional intake was measured before the initial blood sample collection. There were no significant changes in weight, BMI, fat mass, or fat-free mass. There were no significant differences in daily energy consumption, physical activity and nutritional intake. Peripheral blood variables did not change significantly. The drinking of “IZUMI” increased serum BAP level gradually, and after 30 days it was significantly higher as compared to the pre-drinking level. The serum level of d-ROM and blood filtration time (BFT) decreased by drinking “IZUMI”; with d-ROM significantly lower than the pre-drinking level after 30 days and BFT significantly decreased after 60 days (all P<0.05). These results suggest that “IZUMI”, a Kurosu containing a higher level of amino acids, increases antioxidant activity and reduces oxidative stress and blood filtration time in female subjects.